Excited-state locked amino analogues of the green fluorescent protein chromophore with a giant Stokes shift. Issue 66 (26th November 2019) - Zaitseva, Snizhana O.; Farkhutdinova, Dilara A.; Baleeva, Nadezhda S.; Smirnov, Alexander Yu.; Zagudaylova, Marina B.; Shakhov, Aleksander M.; Astafiev, Artyom A.; Baranov, Mikhail S.; Bochenkova, Anastasia V.
Abstract : We design a new class of excited-state locked GFP chromophores which intrinsically exhibit a very large Stokes shift. Abstract : We design a novel class of excited-state locked GFP chromophores by introducing an amine group at the double exo -bond and a difluoroboryl bridge. We show that these chromophores intrinsically exhibit a very large Stokes shift of 1 eV. Further tuning through chemical modifications of their aryl substituents makes them environmentally sensitive.